The financial cost of injuries and their association with team success in professional men's cricket - Williams, A.; Peirce, N.; Griffin, S.; Langley, B.; Goggins, L.; McKay, C.; Stokes, K.; Williams, S. (Journal of Science and Medicine in Sport, 2025)
Objectives To quantify the direct and indirect costs associated with injuries in professional men's cricket from 2015/16 to 2021/22 and to report the association between the cost of injuries and team success.